(untitled) (Research, Society and Development, 2022)
Objective: To trace the epidemiological profile of individuals vaccinated in the year 2021 in the municipality of Jaraguá do Sul, SC. Methods: This is a cross-sectional study with a quantitative approach. The population was composed of individuals vaccinated against coronavirus, registered in the information system of the Health Department of the city of Jaraguá do Sul/SC, between 01/01/2021 and 31/12/2021. The variables evaluated were gender, age range, types and doses of vaccines, administration period, and neighborhoods of residence. Results/Discussion: The highest prevalence of vaccination was in females (52.2%) and the predominant age group was adults. The neighborhood with the highest vaccination coverage was Ilha da Figueira, with 17,328 people vaccinated, followed by Barra do Rio Cerro with 15,734 and Centro with 15,366. 116,451 individuals were vaccinated with the first dose until December 2021, 109,568 with the second dose, 20,738 received a booster dose, and 6,168 received a single dose. By December 2021, 80.3% of individuals had been vaccinated with the first dose, characterizing the immunity of the herd in the municipality. Conclusions: The importance of this analysis at the municipal level is fundamental in Primary Care, because it allows the application of prevention, promotion, and health education measures.